Determinants of Avoidable Deaths from Ischaemic Heart Diseases in East and West Germany - Christoph Schwierz; Ansgar Wübker (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
The objective of this paper is to identify selected forces of the decrease in the number of avoidable deaths from ischaemic heart diseases (IHD) inWest and East Germany from 1996 to 2004. Our main result reveals that the number of intracardiac catheter facilities,which are an important diagnostic tool for IHD, do significantly account for decreases in avoidable mortality from IHD.This is important, as the modernization of the East German health sector included a considerable catch-up process in the number of IC facilities provided relative to West Germany.
Keywords: I12; I19; 330; Avoidable deaths; ischaemic heart disease; intracardiac catheters; Germany; Herzkrankheit; Sterblichkeit; Medizintechnisches Gerät; Wirtschaftliche Anpassung; Alte Bundesländer; Neue Bundesländer; Deutschland